AYOLLARDA PERINATAL DAVRDAGI PSIXOEMOTSIONAL HOLATLAR DIAGNOSTIKASI: METODIKALAR TASNIFI - Kalandarova, M.B. (SCIENCE and SOCIETY, 2022)
The article analyzes the need to study psycho-emotional states in women in the perinatal period and provide psychological assistance when negative emotional states are detected. From the point of view of the biopsychosocial approach in the psychology of the reproductive sphere, the specificity of women’s experiences in the perinatal period requires a special study of the developmental factor of anxiety-depressive symptoms in this period. A modern set of methods for psychodiagnostics of emotional states and detection of negative emotional states in women in the gestational and postpartum periods is presented.